2011
DOI: 10.1007/s12539-011-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

Which value should be used as the lethal concentration 50 (LC50) with bacteria?

Abstract: Computations of lethal concentration 50 (LC(50)) of a data-set of a toxicity study on an herbicide against a cyanobacterium were performed by general linear regression, Spearman-Karber and probit transformation methods, for evaluation of the methods used. It is shown that the linear regression method yields some faulty LC(50) value, while both of Spearman-Karber and probit methods yield similar and statistically respectable LC(50) values. In the Spearman-Karber method, a prerequisite of some uniform dose-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The toxicology test with Artemia is presented in Figure . The lethal concentration was calculated with two different techniques, Probit analysis and mortality in function of log­([C 2 mim]­[CH 3 SO 3 ]). , The two methods agree very well, and the average lethal concentration seen in Table is 4.833 ± 0.001 mg/L. The lower LC 50 is indicative of increased toxicity, meaning that 4.833 mg/L of [C 2 mim]­[CH 3 SO 3 ] makes it more toxic when compared to an organic solvent, such as ethylene glycol, with an LC 50 of 112 mg/L .…”
Section: Resultsmentioning
confidence: 99%
“…The toxicology test with Artemia is presented in Figure . The lethal concentration was calculated with two different techniques, Probit analysis and mortality in function of log­([C 2 mim]­[CH 3 SO 3 ]). , The two methods agree very well, and the average lethal concentration seen in Table is 4.833 ± 0.001 mg/L. The lower LC 50 is indicative of increased toxicity, meaning that 4.833 mg/L of [C 2 mim]­[CH 3 SO 3 ] makes it more toxic when compared to an organic solvent, such as ethylene glycol, with an LC 50 of 112 mg/L .…”
Section: Resultsmentioning
confidence: 99%
“…The LC 50 was determined by linearly fitting (least squares method) the two data points closest above and below 50% cell viability, with axes scaled logarithmically in x and linearly in y . It was shown that LC 50 determination using other methods (e.g., Probit) is more accurate; however, any differences in LC 50 due to applying different fitting methods is expected to be lower than the uncertainties induced by the limited number of different concentrations per sample ( n = 4–6) and the use of average dose–response curves for each combustion condition with standard deviations for the cell viability of up to 35%.…”
Section: Methodsmentioning
confidence: 99%
“…Toxicity values were obtained with different concentrations of PbCl 2 and lead acetate ( Figure 4 ). Percent lethality (PL) values of the third repeated experiment were transformed to probit values by Finney’s method, which were potted against corresponding log 10 values of PbCl 2 and lead acetate concentrations, as exemplified before (Rath et al ., 2011 ). Probits of observed lethality percentage values were from statistical tables of probit transformation.…”
Section: Methodsmentioning
confidence: 99%